2008
DOI: 10.1097/01.nna.0000312771.96610.df
|View full text |Cite
|
Sign up to set email alerts
|

The Balancing Act

Abstract: Findings indicate a huge opportunity to both improve clinical outcomes in these units and, at the same time, reduce costs by focusing on processes to reduce the high amount time spent performing NVA and support activities and increase patient care time, particularly patient teaching and psychosocial support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…On the positive side, the study found that 25.5% of the time of the nursing unit managers is spent on patient care. Although this proportion compares well with the findings of studies among nurses providing direct care in high-income countries ( 17 , 19 , 20 , 24 , 33 ), this proportion might not be appropriate in light of the core management responsibilities of nursing unit managers. The study also found that unit managers experienced numerous interruptions, performing many short, fragmented tasks.…”
Section: Discussionmentioning
confidence: 44%
See 2 more Smart Citations
“…On the positive side, the study found that 25.5% of the time of the nursing unit managers is spent on patient care. Although this proportion compares well with the findings of studies among nurses providing direct care in high-income countries ( 17 , 19 , 20 , 24 , 33 ), this proportion might not be appropriate in light of the core management responsibilities of nursing unit managers. The study also found that unit managers experienced numerous interruptions, performing many short, fragmented tasks.…”
Section: Discussionmentioning
confidence: 44%
“…Similarly a Belgian study found that nurses spent 32.2% of their time on direct patient care ( 24 ), while a similar proportion of 32.8% was found in a Montreal hospital study among surgical nurses ( 17 ). The 1934 US study found that ‘head nurses’ or unit managers spent around 15.6% of their time on direct patient care ( 30 ), while another US study found that nurses spent 44% of their time on patient care ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As it has become more common for nursing units to be understaffed and/or overworked (Anderson, 2007;Hassmiller & Cozine, 2006;Shindul-Rothschild, Berry, & Long-Middleton, 1996), it is important to consider how nursing staff can potentially use their time more efficiently and more effectively (Hendrich, Chow, Skierczynski, & Lu, 2008;Storfjell, Omoike, & Ohlson, 2008). One of the most desired goals in acute care is to increase the amount of time a nurse is able to interact with and directly care for a patient.…”
Section: Nurse Presence In Patient Roomsmentioning
confidence: 98%
“…This is in line with the findings of a study by Mark et al, which stated that costs were increased when many registered nurses were hired in the hospital [ 9 ]. Nonetheless, although the salary of registered nurses was high and found to contribute to the high cost of treatment, knowledgeable and highly skilful nurses are important for a positive patient outcome [ 10 ].…”
Section: Introductionmentioning
confidence: 99%